Как вы упростите \(12a (a^2 + b) - 5b (b^2 + a) + 9b (b^2 + a) - 3a (a^2 + b)\)?

0
0

Как вы упростите \(12a (a^2 + b) — 5b (b^2 + a) + 9b (b^2 + a) — 3a (a^2 + b)\)?

0
0

\[9a^3 +13ab +4b^3\] Объяснение:

Шаг первый: разверните скобки \[12a(a^2+ b) — 5b(b^2+a) + 9b(b^2 + a) — 3a(a^2 +b) =\] \[(12a)(a^2) + (12a)(b) (-5b)(b^2)+(-5b)(a)+(9b)(b^2)+(9b)(a)(-3a)(a^2)+(-3a)(b) =\] что дает нам \[12a^3+12ab-5b^3-5ab+9b^3+9ab-3a^3-3ab\] Шаг второй: собрать как термины \[(12a^3)-5b^3-5ab+9b^3+9ab ( -3a^3)-3ab=
(9a^3)-5b^3-5ab+9b^3+9ab-3ab\] \[9a^3+(12ab)-5b^3(-5ab)+9b^3(+9ab) (-3ab) = 9a^3 + (13ab)-5b^3+9b^3\] \[9a^3+13ab(-5b^3)+(9b^3)= 9a^3 +13ab +(4b^3)\] Ответ: \[9a^3 +13ab +4b^3\]

Показан 1 результат